Travel Routes, Harvesting and Climate Change in Ulukhaktok, Canada - Pearce, T; Smit, B; Duerden, F; Kataoyak, F; Goose, A; Inuktalik, R; Ford, J; Wandel, J (Northern Research Forum (NRF), 2008)
This paper presents research that integrates natural and social science data with the knowledge from community members to document the implications of climate change for travel routes, used by community members in Ulukhaktok to access seasonal harvesting grounds, and how policy decisions can enhance capacity to adapt in the future. It outlines steps for engaging arctic communities in climate change research and describes an approach to assessing vulnerability. The approach is applied in a case study for the community of Ulukhaktok, Northwest Territories (NT), Canada. Information was collected from a triangulated set of resources including, community reports, climate records, existing research, and 62 in-depth interviews with community members. Data indicates that climate change together with societal changes have resulted in compromised trail routes to harvesting grounds and increased hazards for travelers. Current adaptive strategies involve traveling via alternative modes of transportation and travel routes, taking extra precautions before and during travel and sharing country foods. Adaptations are not universal among community members and changing trail conditions have resulted in community members spending less time traveling on the land harvesting country foods which has implications for food security, local economy, cultural preservation and health.